2021
DOI: 10.1097/bsd.0000000000001224
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Risk Factors Associated With Distal Junctional Failure in Adult Spinal Deformity Surgery

Abstract: Background: The surgical management of adult spinal deformity (ASD) is a major surgical undertaking associated with considerable perioperative risk and a substantial complication profile. Although the natural history and risk factors associated with proximal junctional kyphosis (PJK) and proximal junctional failure are widely reported, distal junctional failure (DJF) is less well understood.Study Design: A systematic review was carried out.Objectives: The primary objective is to identify the risk factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Late complications experienced were DJF [4/20 (20%)], PJK [8/20 (40%)], PJF [1/20 (5%)]. This is higher than the reported DJF rate of 3.6% but less than the reported PJF rate of up to 35% ( 17 , 19 ). Our cohorts PJK rate was less than findings that over half of ASD surgical patients develop PJK ( 20 ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Late complications experienced were DJF [4/20 (20%)], PJK [8/20 (40%)], PJF [1/20 (5%)]. This is higher than the reported DJF rate of 3.6% but less than the reported PJF rate of up to 35% ( 17 , 19 ). Our cohorts PJK rate was less than findings that over half of ASD surgical patients develop PJK ( 20 ).…”
Section: Discussionmentioning
confidence: 85%
“…McDonnell et al [2021] stated that anterior-posterior (versus posterior-only) surgery, fusion to the sacrum, and younger age (<60 years) were protective of DJF with conventional rod use. The need for an interbody fusion at L5/S1 is controversial with conflicting reports about the benefit and complication rate ( 17 ). In our series, all patients who suffered DJF reported high decisional regret.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that although the incidence of DJPs is lower than that of PJK/PJF, affected patients are more likely to require revision surgery when they occur 8,9 . The pathogenic mechanisms underlying DJPs are multifactorial, and older age, 7 large preoperative sagittal parameters, 10 fusion short of including the first lordotic disc, 11 selection of the incorrect lowest instrumented vertebra (LIV), 12,13 and inability to match the postoperative sagittal plane with the pelvic incidence (PI) 14 have been reported to be involved. Recently, lower muscularity and higher fatty degeneration have been reported as risk factors for PJK 15 .…”
Section: Introductionmentioning
confidence: 96%
“…The natural history and risk factors associated with proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) have widely reported, 4–6 but distal junctional problems (DJPs), including distal junction kyphosis/failure (DJK/DJF), have rarely been reported in the literature. A systematic review of 12 studies showed that the incidence of DJF was only 3.6%, but it represented 27.3% of all revision surgeries 7 . This finding indicates that although the incidence of DJPs is lower than that of PJK/PJF, affected patients are more likely to require revision surgery when they occur 8,9 .…”
Section: Introductionmentioning
confidence: 99%